Carne Bovina: Produtividade Vs Qualidade - Golmia, Marcelo Curiati [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Bovine meat exerts an important contribution to the human diet, mainly by its high biological value. For this reason the productivity and the quality of beef are so discussed. Productivity is defined as the ratio between production and the factors of production used and quality defined as an adjective given to the product that suits the consumer implicit and explicit. Brazil is the world leader in tonnage exported bovine meat, however the country has a relatively low income, since no exports to the markets of greater added value. Quantify the degree of importance of these two factors in a capitalist market is not easy, so knowing the science that involves this product is vital for both factors. We must know that there is a wide variability in the markets importers and Brazil should seek to be the leader everywhere, whether carcass with better conformation and degree of finish, is lean beef, organic meat is even

A carne bovina exerce uma contribuição importante na dieta humana, principalmente pelo seu alto valor biológico. Por esse motivo a produtividade e a qualidade da carne bovina são tão discutidas. Produtividade definida como a relação entre a produção e os fatores de produção utilizados e qualidade definida como um adjetivo dado ao produto que satisfaça as necessidades implícitas e explícitas dos consumidores.O Brasil é o líder mundial em tonelagem de carne bovina exportada, porém o país tem uma renda relativamente baixa, já que não exporta para os mercados de maior valor agregado.Quantificar o grau de importância destes dois fatores em um mercado capitalista não é fácil, portanto conhecer a ciência que envolve este produto é fundamental para ambos os fatores.Devemos ter em mente que há uma grande variabilidade nos mercados importadores e o Brasil deve procurar ser o líder em todos eles, seja carne com maior grau de acabamento, seja carne magra, seja até mesmo carne orgânica
Keywords: Carne bovina; Carne - Qualidade